Perspectiva teórica de los elementos del marketing que permiten optimizar los servicios universitarios - Baca-Neglia, América Silvia; Blanco-Jiménez, Mónica; Galindo-Mora, Patricio (Universidad Autónoma de Nuevo León, 2018)
El ?????????s.